PERAN SEKOLAH GAJAHWONG TERHADAP PEMENUHAN HAK PENDIDIKAN ANAK KELOMPOK MASYARAKAT MARGINAL - Tri Isnaeni Ades Ria; Ashfi Mazida Mauila; Aura Azahra; Muhammad Ardiansyah (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
This study aims to analyze the role of Gajahwong School as a manifestation of humanist education in fulfilling the right to education of children from marginalized communities. This research uses a qualitative approach with a case study type. Data collection techniques were conducted through interviews with four informants who are facilitators and student guardians, participant observation of learning activities and social interactions at school, as well as documentation in the form of school archives and visual documentation of educational activities. The results show that Gajahwong School has a significant role in fulfilling the right to education through three main dimensions: first, providing affordable and flexible access to education for children of marginalized groups; second, developing a curriculum that is contextual and relevant to the socio-economic conditions of students; and third, creating a learning environment that is inclusive and free from discrimination. This research concludes that the existence of Gajahwong School contributes to presenting the concept of humanist education for the oppressed such as marginalized communities, as well as becoming an alternative model for the implementation of the right to education.